Supraclavicular lymph node metastasis in esophageal carcinoma: a topic of ongoing controversy - Zhang, Bowen; Zhang, Huan; Chen, Yu; Xia, Wanli; Wang, Yichun (Frontiers in Oncology, 2025)
Lymph node metastasis is an important prognostic factor in esophageal carcinoma (EC). Currently, there are no consensus-based staging methods for EC with supraclavicular lymph node (SCLN) metastasis. In this review, we present a summary of several classification methods of the SCLNs and highlight their differences in anatomic definitions. Then, we analyze the lymphatic drainage of the SCLNs from esophagus and the distribution patterns of the SCLNs metastasis from EC. Moreover, we discuss the prognostic influence and different staging methods of the SCLN metastasis. In summary, the variations in different classification methods make the SCLNs confusing for clinical application. A standardized and precise definition of the SCLNs should be established urgently for EC. SCLNs can drain lymphatics at various levels of the esophagus, even from the intramural esophagus directly. Therefore, the SCLNs can be metastatic in superficial EC and even become sentinel nodes. Metastatic SCLNs are usually located on the surface of the scalenus anterior muscle and near the venous angle. Increasing pieces of evidence have shown that patients with SCLN metastasis have similar survival than those with regional lymph node metastasis and better survival than those with organ metastasis, which bring challenges to current staging methods.